Technology of Information in the Production of Parodies of the Subject of Physics in High School as a Methodological Tool (Research, Society and Development, 2022)
This article aimed to present the feasibility of using Information Technology in the production of parodies as a methodological tool for teaching Physics. For this, two classes of the 8th and 9th Year of High School were chosen from a school in the city of Nova Veneza-Goiânia-GO. It is a qualitative research where the theories of meaningful and critical learning served as theoretical support. Students from these classes participated, with 24 (twenty-four) students, held for a period of 02 (two) months, between September and October 2020. The students were divided into 02 (two) groups of 12 (twelve) members , being encouraged to consult other materials in addition to the teaching materials that the teacher provided them, all via online, to enable the production of parodies. Throughout the process, there was weekly contact between the teacher and the students through the internet, meetings via GoToMeeting, WhatsApp, in order to clarify any doubts. At the end, the students were evaluated by the parodies presented, not being possible to deepen the content due to the COVID-19 pandemic. In the end, the perception of the students' motivation to carry out the proposed activities was concluded, observing their great commitment throughout the period of production of the parodies and with the help of the application. In general, the students showed a conceptual evolution and significant assimilation of new concepts, demonstrating that the developed tool meets the desired purposes.